Physical contact between mesenchymal stem cells and endothelial precursors induces distinct signatures with relevance to the very early phase of regeneration. Issue 11 (13th August 2018) - Hafen, Bettina; Wiesner, Susanne; Schlegelmilch, Katrin; Keller, Alexander; Seefried, Lothar; Ebert, Regina; Walles, Heike; Jakob, Franz; Schütze, Norbert
Abstract: Multipotent adult stem cells/precursor cells, especially of the mesenchymal and endothelial lineage, may have great potential for bone tissue engineering. Although their potential is highly recognized, not much is known about the underlying molecular mechanisms that initiate the regeneration process, connect osteogenesis, and angiogenesis and, finally, orchestrate renewal of bone tissue. Our study addressed these questions by generating two in vitro cell culture models to examine the changes in the global gene expression patterns of endothelial precursor cells and mesenchymal stem cells after 24 hours of either humoral (conditioned medium) or direct cell‐cell interaction (co‐culture). Endothelial precursor cells were isolated from human buffy coat and mesenchymal stem cells from the bone marrow of the femoral head. The comparison of the treated and control cells by microarray analyses revealed in total more than 1500 regulated genes, which were analyzed for their affiliation to angiogenesis and osteogenesis. Expression array analyses at the RNA and protein level revealed data with respect to regulated genes, pathways and targets that may represent a valid basis for further dissection of the systems biology of regeneration processes. It may also be helpful for the reconstitution of the natural composition of a regenerative microenvironment when targeting tissue regeneration both in vitro and in situ. Abstract : Endothelial precursor cells and mesenchymal stem cells were cocultured and separated by fluorescence‐activated cell sorting after coculture (C, D) or receiving conditioned medium of the other cell type (A, B). Subsequent to gene array analyses, clusters of genes with relevance to angiogenesis, osteogenesis, and extracellular matrix were detected. The findings have implications for bone regeneration.